Development of an indirect enzyme-linked immunosorbent assay for the detection of osmotolerant yeast Zygosaccharomyces rouxii in different food - Hong Guo (Taylor & Francis Group, 2018)
A polyclonal antibody-based indirect ELISA for the sensitive and specific detection of osmotolerant Zygosaccharomyces rouxii was established. The reactivity of the polyclonal antibodies (pAbs) with Z. rouxii was confirmed by immunofluorescence. The ELISA detection limit was 5 × 104 CFU/mL. For an evaluation of the specificity of pAbs, reactivity to 10 fungi species and 2 bacteria species commonly found in food environments was analysed by indirect ELISA. ELISA reacts with all tested Z. rouxii, whereas no cross-reactions or weakly reactions with 9 fungi and 2 bacteria were observed. The immunoassay staining confirmed the ELISA. Further on, the assay applicability was tested with concentrated apple juice, wine, and honey. Food samples were inoculated with 100 CFU/mL of Z. rouxii. After enrichment for 24 h, the established ELISA can successfully detect contaminated wine and concentrated apple juice samples, while only 30 h was required for honey samples.